Contrast Induced Nephropathy - A Review - Rajul Rastogi; Prabhat Kumar Bhagat; Yuktika Gupta; Shourya Sharma; Pragya Sinha; Pankaj Kumar Das; Mohini Chaudhary; Vijai Pratap (Archives of Clinical Nephrology - Peertechz Publications, 2017)
In the modern era of widespread utilisation of imaging procedures for preoperative diagnosis and minimal invasive surgeries, intravenous contrast plays a major role in delineation of variety of information related to vascularity of normal as well as abnormal tissues. Vascular structures may themselves be focus of  attention for various vascular interventional procedures, again requiring intravenous contrast. Since the intravenous contrast agent used in the imaging procedures is primarily excreted through kidneys, hence pre-procedural renal function should be adequate not only to facilitate its excretion for preventing effects related to contrast retention in body but also contrast-induced nephrotoxicity. As contrast-induced nephropathy is being increasingly encountered in day-to-day practice recently, hence this article focuses on the different facets of contrast-induced nephropathy secondary to iodinated contrast from etiology, risk factors to management.